Commercial banking : - Gup, Benton E. (J. Wiley, 2005)
From the growth of electronic banking, to the rapid rise in overseas operations, to deregulation and recent laws, Gup and Kolari's Commercial Banking: The Management of Risk, Third Edition will help you understand these new realities and keep up with what's happening in the banking industry. With a strong emphasis on managing risk and maximizing profit, this up-to-date text provides a comprehensive, practical introduction to bank management and current banking practices used to control different kinds of risk. You'll examine the factors that affect the value of a bank and techniques for managing that value including the use of financial derivatives. You'll also explore the principal lending activities to businesses and individuals from the point of view of both the bank and the borrower.